Patient influence in home-based reablement for older persons: qualitative research - Aud Moe; Kari Ingstad; Hildfrid V. Brataas (BMC, 2017)
Abstract Background Reablement services are rehabilitation for older people living at home, being person-centered in information, mapping and the goal-setting conversation. The purpose of this study was to gain knowledge about conversation processes and patient influence in formulating the patients' goals. There are two research questions: How do conversation theme, structure and processes appear in interactions aiming to decide goals of home-based reablement rehabilitation for the elderly? How professionals' communication skills do influence on patients' participation in conversation about everyday life and goals of home-based reablement? Methods A qualitative field study explored eight cases of naturally occurring conversations between patients and healthcare professionals in a rehabilitation team. Patients were aged 67-90 years old. The reablement team consisted of an occupational therapist, physiotherapist, nurse and care workers. Data was collected by audio recording the conversations. Transcribed text was analyzed for conversational theme and communication patterns as they emerged within main themes. Results Patient participation differed with various professional leadership and communication in the information, mapping and goalsetting process. In the data material in its entirety, conversations consisted mainly of three parts where each part dealt with one of the three main topics. The first part was "Introduction to the program." The main part of the talk was about mapping ("Varying patient participation when discussing everyday life"), while the last part was about goal setting ("Goals of rehabilitation"). Conclusions Home-based reablement requires communication skills to encourage user participation, and mapping of resources and needs, leading to the formulation of objectives. Professional health workers must master integrating two intentions: goal-oriented and person-centered communication that requires communication skills and leadership ability in communication, promoting patient influence and goal-setting. Quality of such conversations is complex, and requires the ability to apply integrated knowledge, skills and attitudes appropriate to communication situations.